IbM TAHU BAKSO "ASUH" DI KECAMATAN BOYOLALI KABUPATEN BOYOLALI - Edhi Nurhartadi; R. Baskara Anandito; Bara Yudhistira (Jurnal Kewirausahaan dan Bisnis, 2018)
Tofu meatballs is a snack that is made from tofu as the mayor ingredients with meat dough stuffing through the process of steaming and frying. Tofu meatballs become one of food innovation from tofu which serve delicious taste. EQ company in Karanggeneng Village, Boyolali District has a production capacity of 700-800 tofu meatballs on Monday-Saturday and 400 tofu meatballs on holiday. The problems faced by the home-processing in home industry know meatballs are among others related to the quality of tofu meatballs that have not met the expectations of buyers. Another obstacle faced is the stagnant business conditions due to the lack of product diversification, the equipment used is still limited and simple, the production capacity is minimal, the packing of tofu meatballs produced is also less attractive. Program implemented (1) Introduction of production process know meatballs technology that meets quality management of processed foods ASUH (safe, healthy, whole and halal); (2) Introduction of appropriate technology for the processing of tofu meatballs in the form of refrigerator machinery and other means of production improvement; (3) Introduction of technological variations of packaging materials such as hand sealer machine; (4) Management of Food Industry License (PIRT); (5) Simple marketing and bookkeeping training. This has been set forth in the letter of cooperation agreement. The results of dedication activities that have been done by the dedication team are coordinating with partners about problem solving effort, training on how to make meatball tofu with quality management concept "ASUH" that is safe, healthy, whole and halal. Keywords: ASUH, quality, tofu meatballs, production process, management.